ATLAS-1.0: Atmospheric Lagrangian dispersion model for tephra transport and deposition. (October 2019) - Reckziegel, F.; Folch, A.; Viramonte, J.
Abstract: ATLAS-1.0 (ATmospheric LAgrangian diSpersion) is a new atmospheric dispersion and sedimentation Lagrangian model tailored to volcanic tephra/ash. The model solves the Advection–Diffusion–Sedimentation equation across multiple scales (from regional to global) and can be driven off-line by different numerical weather prediction models in combination. For example, meteorological data from the mesoscale Weather Research Forecast (WRF) model can be combined with data from the Global Forecast System (GFS) so that ATLAS automatically selects the highest resolution data available in any part of the computational domain. ATLAS can be used in forward mode to forecast ash dispersal from a volcano (or from extended sources) or in backward mode to integrate trajectories backwards in time and constrain unknown source term characteristics. Multiple source terms can be defined, e.g. to simulate several eruption phases with different granulometric characteristics on a single model execution. We validate the implementation of the model using the 2011 Cordón Caulle and the 2015 Calbuco eruptions and compare the results with previous simulations performed with the FALL3D model. The code has been designed from scratch to facilitate future parallelization, inclusion of ash resuspension schemes, and ensemble-based probabilistic forecast assimilating data from satellite retrievals. Highlights: ATLAS simulates the atmospheric dispersion of volcanic ash particles. ATLAS admits different particles emission sources and grain size distributions. ATLAS reads global and regional meteorological files. ATLAS is validated using Cordón Caulle 2011 and Calbuco 2015 eruptions. Convergence analysis indicate 1M to 1.5M particles (puff) to simulate eruptions.